Reproductive adaptation of rice to environmental stress (Japan Scientific Societies Press, 1992)
In rice culture, where seed production is the primary objective, the process of spikelet formation is of major interest. The number and development of spikelets which are differentiated by the panicle directly affect the grain yield. Moreover, the spikelet formation process, especially the stage of differentiation and development of generative cells and the flower-fertilization stage, is the most sensitive to environmental stresses. Subjection to environmental stress at this stage results in severe injuries with consequent reduction in the yield. These stresses include temperature stress, physiological stresses associated with soil, high salinity, flood, drought and fungus infection. The response of the plant differs according to the developmental stage at which it experiences the stress. Thus, an understanding of rice reproductive function and physiology is extremely important to make clear how the morphogenesis of rice spikelets, and especial